Efektifitas Beberapa Teknik Pengendalian Setothosea asigna pada Fase Vegetatif Kelapa Sawit di Rumah Kaca - Marjan Sinaga; Syahrial Oemry; Lisnawita Lisnawita (Universitas Sumatera Utara, 2015)
The aim of research was to get an effective control technique to control Setothosea asigna onvegetative phase of palm oil in greenhouse. The research was held at Greenhouse of AgricultureFaculty University of Sumatera Utara, Medan since April – May 2014. The method of this researchwas Completely Randomized Design Non Factorial with seven treatments, M0 (control), M1 (2gram MNPV/ litre of water), M2 (Bacillus thuringeensis with concentration 7.5%), M3 (neem leafextracts with concentration 4%), M4 (Forficulla auricularia three pairs), M5 (insecticidedeltametrin with concentration 3%) and M6 (insecticide dimetoat with concentration 1%)respectively with four replications. The parameters are the percentage of mortality, symptoms deathof pests and time death of pest. The result showed that insecticide deltametrin most effective thanthe others with percentage of mortality 100% at 4 days after application. The fastest time death ofimago was 1.63 day after application with symptoms body of S. asigna was white like milk.Keywords: control technique, Setothosea asigna, mortality, time death